PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION YANG DIMEDIASI KEPUASAN KERJA PADA PT TATA MULIA NUSANTARA INDAH CABANG BALI - Ni Ketut Laswitarni; Ni Putu Marsita Yuli Pratiwi (Forum Manajemen, 2022)
This study intended to the effect of job stress on turnover intention, the effect of job stress on job satisfaction, the effect of job satisfaction on turnover intention and also to determine the role of job satisfaction in mediating the effect of work stress and turnover intention. it takes 51 employees, by using random sampling method. On this study analysis using the path analysis and sobel test. Based on the results of the analytic, the job stress has a positive and significant effect on turnover intention, job stress has a negative and significant effect on job satisfaction, job satisfaction has a negative and significant effect on turnover intention. The results of this study also indicate that job satisfaction mediates job stress on turnover intention. To reduce turnover intention, management should pay more attention to the job descriptions of employees.